Kajian Hukum Pembatalan Putusan Pengadilan Agama tentang Perkawinan yang dilakukan dengan Tipu Muslihat berdasarkan Pasal 71 Huruf (F) Kompilasi Hukum Islam (Perkara No. 3617/Pdt.G/2021/ Pa.Dpk) - Ruslaini, Ruslaini; Arifin, Zaenal; Gozali, Luthfi (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2024)
On September 22 2019 the Petitioner was proposed by Respondent I to be made his wife and plans for his contract in March 2020. However, with the deception carried out by Respondent I and his family to the Petitioner, the Marriage Book Quotation was published Number: 908.67.XII.2019. date, 13 December 2019 issued by Respondent II without the knowledge of the Petitioner as a prospective bride. Because on that day the Petitioner and his mother as well as his two siblings were invited to Mr. De''s house from Respondent I for a family friendly event as well as visiting his Mrs. De' who was ill. Marriage Book Number: 908.67.XI1.2019 dated 13 December 2019 issued by Respondent II, who has never lived in the same house as a husband and wife and the condition of the Petitioner's virginity is still a virgin. Oh, because it's based on Law no. 1 of 1974 regarding Marriage Oo. Book I Compilation of Islamic Law, the Petitioner still has the right to submit the Petitioner in the case aquo; based on these considerations, it can be concluded that there has been a legal mention for the Petitioner to annul the marriage with the Respondent as intended by the elucidation of Article 71 letter (f) of the Compilation of Islamic Law that a marriage can be annulled if the marriage is carried out by coercion Tries, Grants the Petitioner's request ; Canceled the marriage of the Petitioner and the Respondent which was carried out on December 13 2019 with the excerpt of the Marriage Certificate Number 908/67/XM/2019 dated December 13 2019 issued by the District Office of Religious Affairs xxxx xxxx xxxxx; Declare that the Quote of the Marriage Certificate Number 908/67/XI1/2019 dated 13 December 2019 issued by the Office of Religious Affairs of the District of xxxx xxxx xxxxx has no legal force; Charge the Petitioner to pay the costs of this case in the amount of Rp. 380,000,000 (three hundred and eighty thousand rupiah)